The Legal Policy towards the Prevention of the Land Mafia Base of Implementing the Land Registration System - Novita, Ita (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2022)
This study aims to determine the building of a land registration system that is free from land mafia practices, and to identify and analyze obstacles in preventing land mafia in the land registration system. The research approach method used in this journal is the normative juridical research method. The specification of this research uses descriptive analysis. The type of data used in this study is primary data which includes the 1945 Constitution; Act No. 5 of 1960; Basic Agrarian Law; Code of Civil law; The Criminal Code, as well as secondary data containing books and other supporting documents. Collecting research data by studying documents or library materials. The data analysis method used in analyzing the data isnormative or literary research methods, this research is conducted to obtain more in-depth knowledge about the land registration system and the prevention and eradication of the Land Mafia by individuals and/or groups. Based on the research it was concluded that there is a need for a regulation on the system as well as an increase in good supervision by the central government and an increase in certificate products and guarantees of accountability for formal certificate products. Barriers to preventing the land mafia in the land registration system arethe unavailability of a legal umbrella and formation policyalternative dispute resolution (ADR) on land conflict/dispute resolution and the synergy of parties who have special authority in preventing and eradicating the land mafia, namely the Police, Prosecutors' Office, Courts, PANJA Land Mafia.Keywords: Land; Mafia; Registration; System.